2016
DOI: 10.3802/jgo.2016.27.e4
|View full text |Cite
|
Sign up to set email alerts
|

The risk of lymphedema after postoperative radiation therapy in endometrial cancer

Abstract: ObjectiveLower extremity lymphedema adversely affects quality of life by causing discomfort, impaired mobility and increased risk of infection. The goal of this study is to investigate factors that influence the likelihood of lymphedema in patients with endometrial cancer who undergo adjuvant radiation with or without chemotherapy.MethodsA retrospective chart review identified all stage I–III endometrial cancer patients who had a hysterectomy with or without complete staging lymphadenectomy and adjuvant radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 25 publications
3
32
0
Order By: Relevance
“…In other studies the median number of removed lymph nodes is significantly higher, up to over 80 [20,27,28,31]. The number of removed lymph nodes seems to be of importance for developing LLL with an increasing risk for LLL when a larger number of lymph nodes are removed [10,21,22,24,[37][38][39][40][41][42]. Interestingly, and with no obvious reasonable pathophysiological explanation, Hareyama et al found a significantly lower risk of LLL in women when the number of removed lymph nodes exceeded 70 [28].…”
Section: Risk Factors For Lllmentioning
confidence: 92%
See 2 more Smart Citations
“…In other studies the median number of removed lymph nodes is significantly higher, up to over 80 [20,27,28,31]. The number of removed lymph nodes seems to be of importance for developing LLL with an increasing risk for LLL when a larger number of lymph nodes are removed [10,21,22,24,[37][38][39][40][41][42]. Interestingly, and with no obvious reasonable pathophysiological explanation, Hareyama et al found a significantly lower risk of LLL in women when the number of removed lymph nodes exceeded 70 [28].…”
Section: Risk Factors For Lllmentioning
confidence: 92%
“…The occurrence of lymph node metastases in the removed lymph nodes was shown by Mitra et al to be a risk factor for LLL [41], but the results are contradictory [28,43].…”
Section: Risk Factors For Lllmentioning
confidence: 96%
See 1 more Smart Citation
“…Some studies have suggested that radiation increases the risk of lymphedema, but most patients in these studies had more than 20 nodes removed, which might increase the risk of lymphedema per se (39,40). In a recent study, the risk of LLL after post-operative radiation (mainly external beam radiation), evaluated through both objective and subjective evaluations, was associated with lymph node positivity (OR=3,2; 95%CI=1.0007-10·7; p=0.0499) when controlled for lymph-node dissection (41).…”
Section: Incidencementioning
confidence: 99%
“…Risk factors remains to be evaluated in correctly designed and sufficiently powered studies. However, lymphadenectomy per se [4][5][6][7], number of lymph nodes removed [6,[8][9][10][11][12][13][14][15][16] and radiotherapy [3, [7][8][9][10][11]14,[17][18][19][20] seem to be established risk factor. Lymphedema onset may begin immediately after surgery or may be delayed for many years.…”
mentioning
confidence: 99%